We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-4
89
1
avatar+-19 

Another one I need help on...

 Mar 15, 2019
 #1
avatar+101086 
+1

3

a^(-1/2)  =  1 /a^1/2   = 1 / √a

b^3/2  =   √b^3  = b√b

 

So..we have

 

3 ( 1 /√a) ( b√b) =

 

   3b√b

_______               [ also could be written as 3b √ (b / a)  ]

    √a

 

 

cool cool cool

 Mar 15, 2019

14 Online Users

avatar
avatar
avatar